VD_FINDINFO HC / 2017 / 766 vom 26. September 2017 - VD Tribunal cantonal (2017)
CONTRAT D'ENTREPRISE, TRAVAUX PRÉPARATOIRESTYPE DE DOCUMENT, RÉSILIATION, DÉLAI | 366 al. 2 CO, 377 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)